The Flexural Behavior of the Full Height Rectangular Opening Castellated Steel Beam with Diagonal Stiffener - Muhamad Rusli Ahyar; Rachmat Mudiyono (International Conference on Coastal and Delta Areas, 2017)
The full height rectangular opening of castellated steel beam is failed in Vierendeel mechanism. The Vierendeel failure mechanism made the load capacity of castellated steel beam is lower than its original section. In this research, the 16 mm diameter of steel bar as the diagonal stiffener is used as a reinforcement on the full height rectangular opening of castellated steel beam has a purposes to prevent Vierendeel failure mechanism so the load capacity of castellated steel beam can reach its maximum capacity. This research used a specimen of 3059 mm long span of castellated steel beam to study the flexural behavior. The specimen will be given the static load until it reached its maximum capacity. The test result show that the load capacity of the castellated steel beam is increase 157% compare to its original section. From the theoretical calculation it has 6.15% difference from the laboratory test result. Keywords: castellated, Vierendeel, flexural behavior